PENERAPAN APLIKASI PELAYANAN SEWA MOBIL DI KOTA SUBUSSALAM BERBASIS ANDROID - Suhendar -; Muhammad Syahputra Novelan (LPPM Politeknik LP3I Medan, 2020)
With the design of a car rental service application based on Android, it makes it easier for consumers to make car reservations. Nowadays information media with technology support is needed, especially with Information technology is increasingly modern, the easier it is for each company to exchange information. Technological developments can be felt with more and more website-based services that make it easier for parties companies and customers only connected to a computer network or internet media. In the past, information and communication was carried out Simply put, with the support of this modern information media a lot The company's management system has been supported by a website-based application. The development and construction of a new system can improve the company's performance in the car rental or rental process, namely the new system which is supported and designed specifically for car rental process management. With Android smartphone media, customers don't have to bother coming directly, simply by connecting via a network connection the order can accepted by the company. For employees, it can automatically register because has been supported by computerized database media to present reports and data entry